ANTIBACTERIAL EFFICACY OF NISIN AS AN IRRIGANT AGAINST ENTEROCOCCUS FAECALIS BIOFILM - HARYANTI, THERESIA PEGGY; NAZAR, KAMIZAR; MARGONO, ANGGRAINI (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to compare the antibacterial efficacy of 10% nisin, 2% chlorhexidine (ChX), and 2.5% sodium hypochlorite (NaOCl) against Enterococcus faecalis biofilm in vitro. Methods: Petri dishes containing brain heart infusion agar were seeded with E. faecalis (ATCC 29212) and were incubated overnight at 37°C. The cellulose nitrate filter membrane was inoculated with E. faecalis for 72 h to grow a biofilm, and we performed the direct contact test between the test solutions and the biofilm for 10 min. The DNA was quantified using real-time polymerase chain reaction with propidium monoazide additive to count the living cells. Results: The number of E. faecalis bacteria in the 2% ChX group was the lowest (8.36×103 CFU/mL) while the highest number of bacteria - among the antibacterial substances tested - in the nisin 10% group (5.55×106 CFU/mL). Conclusion: The antibacterial effects against E. faecalis biofilm of 10% nisin were not comparable with those of 2% ChX and 2.5% NaOCl.